PENGARUH HB IBU HAMIL TERHADAP BERAT BADAN BAYI - Harindra; Rosita, Neng (UPT PPM Sekolah Tinggi Ilmu Kesehatan Al Irsyad Al Islamiyyah Cilacap, 2020)
ABSTRACT Stunting or stunted body growth is a form of malnutrition characterized by height for age below the standard deviation (<-2 SD). (WHO, 2005). Stunted children have an IQ of 5-10 points lower than normal children (Henningham, H.B & McGregor, 2005). West Bangka Regency, Bangka Belitung Islands Province is 1 of 100 priority intervention locations for stunting reduction in 2018 (Director General of Public Health, 2018). Based on the 2013 Riskesdas data, the incidence of stunting in West Bangka Regency was 5,999, with details of 3,319 children aged 0-1 years and 2,680 children aged 1-2 years spread across 10 villages, namely Ibul Village, Air Nyatoh, Peradong, Pangek, Simpang Tiga, Berang in Simpang Teritip District; Tuik and Tugang Villages in Kelapa District; Rukam and Tumbak Petar Villages in Jebus District. This type of research is an explanatory research (Explanatory Research). The research method is a survey with a cross-sectional approach because the causal variables that occur in the research object are measured and collected at the same time. This research uses a quantitative approach. Based on the results of the Rank Spearman Correlation test, the relationship between hemoglobin levels and birth weight (r = 0.018; p = 0.899) means that hemoglobin levels are not related to birth weight. Keywords: Mother's Hemoglobin, Baby Weight